EVALUATION OF ANXIOLYTIC ACTIVITY OF METHANOLIC EXTRACT OF SAPINDUS MUKOROSSI GAERTN. IN MICE - AVIJIT CHAKRABORTY; P. AMUDHA; M. GEETHA; N. SURJIT SINGH (International Journal of Pharma and Bio Sciences, 2010)
The present study was undertaken to evaluate the anxiolytic activity of methanolic extract of Sapindus mukorossi Gaertn.(Sapindaceae). The anxiolytic activity was evaluated by Elevated plus maze, Y-maze, Hole-board, Actophotometer, and Marble-burying behavior models. The efficacy of the extract (200 and 400 mg/kg) was compared with the standard anxiolytic drugs Diazepam (2 mg/kg) and Fluoxetine (10 mg/kg). The result showed that the extract significantly increased the number of entries and time spent in the open arm in the elevated plus maze. The results also showed that the extract significantly increased the number of head dipping and line crossing, decreased the numbers of visits to the three arms, locomotor score and number of marble-buried in Hole-board, Y-maze, Actophotometer and Marble-burying behavior models respectively. Present study confirms that the extract showed significant anxiolytic activity at both dose levels which is comparable with standard anxiolytics Diazepam and Fluoxetine.